Replicating the Procedure Call Abstraction - Ladin, Rivka; Mazer, Murray; Wolman, Alec (Second Workshop on the Management of Replicated Data, 1992)
The authors recommend replicating the procedure call abstraction as a method for constructing highly available distributed programs. In order to make highly available systems much more widespread than they are today, one must make it easier for application developers to incorporate replication into one's systems. Given that remote procedure call has proven to be a useful abstraction in building distributed programs, replicated procedure call seems to be an appropriate method for introducing high availability while hiding the complexities of replication. The authors argue that the simplicity and familiarity of the procedure call mechanism makes it an excellent model for introducing replication, and they discuss different choices one can make in designing a replicated procedure call system.